International to domestic price transmission in fourteen developing countries during the 2007-08 food crisis - Kenneth Baltzer (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
This paper synthesizes the evidence on price transmission from international maize, rice and wheat markets to domestic markets in fourteen developing countries during the global food crisis in 2007-08. A great variation in the price transmission patterns is observed; from almost no price pass-through in China and India, over close relationship between international and domestic prices in Brazil and South Africa, to substantial domestic price overshooting in Ethiopia and Nigeria. Much of this variation can be explained by price stabilization policies, public policy failure, incomplete market integration, and coinciding domestic shocks.
Keywords: F1; O5; 330; Price transmission; global food crisis; cereal prices; Lebensmittelpreis; Getreidepreis; Preiskonvergenz; Ernährungssicherung; Entwicklungsländer